Seasonal factors affecting sea turtle nesting in the Southeastern Caribbean Sea (Gulf of Paria, Venezuela) (Ocean and Coastal Research, 2022)
The nesting characteristics (number of nests and eggs, time of year, nesting initiation, and nesting length) of leatherback (Dermochelys coriacea) and hawksbill (Eretmochelys imbricata) sea turtles of the southern Caribbean Sea (specifically in the Gulf of Paria in Venezuela), were examined in association with weekly precipitation averages and number of rainy days per week during the period between 2009 and 2018. We hypothesized about the influence of rainfall intensity and patterns as the main abiotic factor for sea turtle nesting. On average, leatherbacks preferred nesting during the drier season of each year (March, April, and May), while hawksbills nested during the rainy season (June to September). For both species, we found few significant correlations between the number of nests or clutch size (number of eggs per nest) and weekly averages of seasonal precipitation rates in the region. Average hawksbill clutch sizes were not correlated with average precipitation rates but were positively correlated with the number of rainy days per week (r=0.66, P≤0.05). Average hawksbill clutch sizes decreased each year on average (-3.3 eggs/year, r=-0.88, P≤0.001), which coincided with a negative long-term trend in the number of rainy days (-0.11 rainy days/week, r=-0.69, P≤0.05). During the study period, nesting activities for both leatherback and hawksbills started progressively later (0.9 and 0.6 weeks/year, respectively p≤0.05) and were shorter (-0.9 and -0.8 weeks /year, P≤0.1 and P≤0.05, respectively).